Kedudukan Agama dan Negara: Perspektif Pemikir Muslim Abad Pertengahan Ibn Taymiyyah - Sirojudin Aly (Himpunan Peminat Ilmu-Ilmu Ushuluddin (HIPIUS), 2015)
This articleis trying to discover the political opinion—in terms of relations of religion and state—of an Islamic thinker, Ibn Taymiyya, within the era of Middle Age in the history of Islam. The government experiment in accordance to Islamic teaching had begun since the time of Muḥammad p.u.h. governed the society of Madīna. The leadership then was continued by Khulafā’ al-Rāshidīn after the Prophet Muḥammadpassed away. The system of al-khilāfa then no longer existed and soon changed becoming the monarchy, beginning from the era of Umayyad. This situation could be easily seen in the system of electing the head of the state or the leader of the governmentthrough direct pointing by the on going khalīfa to the candidate who had beenprepared as a prince long before the changingtime.This system of changing the leader of the goverment would be much different from the system in the era of Khulafā’ al-Rāshidīn, where a khalīfa should be selected by a kind of committee consisting of outstanding persons of the society and the men around (saḥāba) the Prophet Muḥammad. In the modern era and contemporary world like nowadays, the goverment model and its system are varied.Religions and politic in the perspective of Islam is integrating in the Classic and Middle Age, while in the modern era there has been emerged the idea to separate the Islamic teaching from the political field.